Personalized Postpartum Interventions and Their Impact on Working Mothers (Media Kesehatan Masyarakat Indonesia, 2025)
Exclusive breastfeeding is a critical determinant in maintaining infant health and nutritional status. However, its coverage remains low, particularly among postpartum working mothers. Limited maternal knowledge, lack of family especially spousal support, and low maternal satisfaction are reported key factors contributing to suboptimal breastfeeding practices. This quasi-experimental study employed a non-equivalent control group pre-test and post-test design. It was conducted from January to October 2024 in the working area of the Darussalam Primary Health Center in Medan, Indonesia. A total of 140 postpartum working mothers were purposively selected and divided into two groups: intervention (n=70) and control (n=70). The intervention group received PBE through a pocketbook, educational videos, and personalized counseling provided by trained midwives. They were followed up at day 7, month 1, month 3 and month 6 post-intervention. Data were analyzed using paired t-test, independent t-test, and repeated measure ANOVA. The exclusive breastfeeding adequacy score significantly increased in the intervention group (p=0.000; p
Keywords: Exclusive Breastfeeding; Working Mothers; Maternal Knowledge; Maternal Satisfaction; Spousal Support